Antiviral Efficacy of Tenofovir Monotherapy in Children with Nucleos(t)ide-naive Chronic Hepatitis B - Choe, Jae Young (J Korean Med Sci, 2017)
BACKGROUND: The purpose was to compare the efficacy between tenofovir disoproxil fumarate (TDF) and lamivudine (LMV) in children with nucleos(t)ide-naive chronic hepatitis B (CHB) infection. Patients with CHB were treated with TDF in the immune-reactive phase and compared with a historical control group of patients treated with LMV before the TDF era. METHODS: Hepatitis B virus (HBV) DNA titer decrements (> 3 log(10) IU/mL) were monitored after treatment initiation. The treatment duration for HBV DNA clearance (< 357 IU/mL) and complete response (HBeAg loss and HBV DNA clearance) were analyzed. The follow-up period was 96 weeks. RESULTS: Sixteen patients were treated with TDF and compared with a historical control group of 24 patients treated with LMV. HBV DNA decrement (> 3 log(10) IU/mL) was achieved in 100% (16/16) of the TDF group but in only 62.5% (15/24) of the LMV group (P = 0.005) at 48 weeks. The HBV DNA clearance (< 357 IU/mL) in the TDF and LMV groups was, respectively, as follows: 62.5% (10/16) and 25.0% (6/24) at 12 weeks (P = 0.018), 81.3% (13/16) and 37.5% (9/24) at 24 weeks (P = 0.006), 93.8% (15/16) and 50.0% (12/24) at 48 weeks (P = 0.004), and 100% (16/16) and 54.2% (13/24) at 96 weeks (P = 0.001). Complete response occurred in 41.7% (5/12) of HBeAg-positive patients in the TDF group and 28.6% (6/21) of the LMV group at 96 weeks (P = 0.443). CONCLUSION: TDF monotherapy for 96 weeks produced a significantly more effective virologic response than LMV monotherapy in children with nucleos(t)ide-naive CHB.